2010
DOI: 10.1002/mnfr.201000140
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde‐modified β‐lactoglobulin AGEs are unable to stimulate inflammatory signaling pathways in RAGE‐expressing human cell lines

Abstract: Our results demonstrate that glycolaldehyde-modified AGEs are unable to induce inflammatory signaling in receptor for AGE-expressing cells. The observed cell-activating activity can be ascribed to an endotoxin-like lipophilic contamination present in AGE preparations and affinity column purification was insufficient to remove this contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…Despite the scientific need for LPS removal to establish the immunological activity of natively folded proteins, only few studies reported on the experimental conditions that affect the efficiency of endotoxin removal from protein extracts using TX-114. Reported protocols vary in incubation conditions and TX-114-removal strategies after LPS-extraction [11, 16, 17, 32], which we have shown to critically influence the application of the purified protein in in vitro assays [26]. Lopes et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the scientific need for LPS removal to establish the immunological activity of natively folded proteins, only few studies reported on the experimental conditions that affect the efficiency of endotoxin removal from protein extracts using TX-114. Reported protocols vary in incubation conditions and TX-114-removal strategies after LPS-extraction [11, 16, 17, 32], which we have shown to critically influence the application of the purified protein in in vitro assays [26]. Lopes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previously published procedures often disregard this phenomenon giving rise to conclusions based on TX-114 induced bias in concentration assays [11, 23, 26, 43]. Buetler and colleagues [11] showed that glycolaldehyde-modified BLG preparations were unable to induce inflammatory signaling in receptor for RAGE-expressing cells after TX-114 assisted extraction of LPS. The authors concluded that cell activation shown for non-treated preparations was connected to a LPS-like lipophilic contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of AGEs with their specific cell surface receptors RAGE may result, among others, in the production of reactive oxygen species and induction of micro-inflammation, which may in turn accelerate the formation of AGEs, and exacerbate insulin resistance [2], [22], [23]. However, some studies have disputed these findings: there are still controversies on the identity of the actual AGEs that initiate the RAGE-mediated reactions, and questions regarding evidence that endotoxin contamination of AGE protein preparations compromised the results of some studies [24], [25]. Experimental studies show that AGEs per se may initiate the insulin-resistant state in skeletal muscle and adipocytes [26][28], or decrease the insulin content and secretion in pancreatic islets [29]–[31].…”
Section: Introductionmentioning
confidence: 99%
“…An interaction between endotoxins and the AGE receptor system exists (28) and endotoxin-like products might contaminate AGE preparations (29). While intravenous administration of endotoxins induces severe toxicity in mammals, oral administration of a high dose of lipopolysaccharides caused no toxicity or systemic inflammation (30), probably due to poor endotoxin absorption (31).…”
Section: Discussionmentioning
confidence: 99%